2015
DOI: 10.1055/s-0034-1398389
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis: Evolving Concepts in Epidemiology, Pathogenesis, and Treatment

Abstract: Infection with Burkholderia pseudomallei can result in asymptomatic seroconversion, a single skin lesion that may or may not heal spontaneously, a pneumonia which can be subacute or chronic and mimic tuberculosis or rapidly progressive resulting in fatal overwhelming sepsis. Latency with subsequent activation of disease is well recognized, but very uncommon. Melioidosis also has a myriad of other clinical presentations and diagnosis is often delayed because of this and because of difficulties with laboratory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
347
1
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(385 citation statements)
references
References 155 publications
5
347
1
17
Order By: Relevance
“…The study from Australia showed that the mortality of bacteremic patients had a mortality rate similar to that of the present study (47%) [8]. The bacteremic form of melioidosis was a severe form and had a high mortality rate, as in the present study [7][8][9][10][11]. This study also showed that three factors associated with death included pulmonary presentation, blood urea nitrogen level, and white blood cell count.…”
Section: Discussionsupporting
confidence: 85%
“…The study from Australia showed that the mortality of bacteremic patients had a mortality rate similar to that of the present study (47%) [8]. The bacteremic form of melioidosis was a severe form and had a high mortality rate, as in the present study [7][8][9][10][11]. This study also showed that three factors associated with death included pulmonary presentation, blood urea nitrogen level, and white blood cell count.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with two well-described features of infection by B. pseudomallei. First, significant numbers of the population in the two main regions of endemicity (tropical Australia and Thailand) are seropositive, although the seropositivity rates in these two regions differ greatly (34). However, although indicating infection by B. pseudomallei, there is great uncertainty regarding the relationship between such prior infection and current latent infection (34).…”
Section: Discussionmentioning
confidence: 99%
“…Infection has been reported in all ages, including neonates and the elderly. Risk factors include farming, especially rice farming, cultivation, military, construction and use of untreated water sources [10].…”
Section: Epidemiologymentioning
confidence: 99%
“…B. pseudomallei may be considered a free-living inhabitant of soil and water and an accidental, opportunistic pathogen that only infects the human host when there is lowered resistance in the host or when there are favourable transmission dynamics eg large dose, traumatic inoculation, aerosolisation, aspiration etc [10].…”
Section: Transmission and Infectionmentioning
confidence: 99%
See 1 more Smart Citation